(w-2)(4w-4)=

Simple and best practice solution for (w-2)(4w-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w-2)(4w-4)= equation:


Simplifying
(w + -2)(4w + -4) = 0

Reorder the terms:
(-2 + w)(4w + -4) = 0

Reorder the terms:
(-2 + w)(-4 + 4w) = 0

Multiply (-2 + w) * (-4 + 4w)
(-2(-4 + 4w) + w(-4 + 4w)) = 0
((-4 * -2 + 4w * -2) + w(-4 + 4w)) = 0
((8 + -8w) + w(-4 + 4w)) = 0
(8 + -8w + (-4 * w + 4w * w)) = 0
(8 + -8w + (-4w + 4w2)) = 0

Combine like terms: -8w + -4w = -12w
(8 + -12w + 4w2) = 0

Solving
8 + -12w + 4w2 = 0

Solving for variable 'w'.

Factor out the Greatest Common Factor (GCF), '4'.
4(2 + -3w + w2) = 0

Factor a trinomial.
4((1 + -1w)(2 + -1w)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(1 + -1w)' equal to zero and attempt to solve: Simplifying 1 + -1w = 0 Solving 1 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1w = 0 + -1 -1w = 0 + -1 Combine like terms: 0 + -1 = -1 -1w = -1 Divide each side by '-1'. w = 1 Simplifying w = 1

Subproblem 2

Set the factor '(2 + -1w)' equal to zero and attempt to solve: Simplifying 2 + -1w = 0 Solving 2 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1w = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1w = 0 + -2 -1w = 0 + -2 Combine like terms: 0 + -2 = -2 -1w = -2 Divide each side by '-1'. w = 2 Simplifying w = 2

Solution

w = {1, 2}

See similar equations:

| 22x-12=6x-10 | | 10(3b+c-6a)-8(a-8c+9b)= | | 6y-8=4y+12 | | -6x^2/(x-2)(x+9) | | 3x^2+16y^2-48=0 | | 12/4+6/1 | | -25y+26=0 | | -5.2x^2+65x-75=0 | | 15-2f=9 | | (4x-5x+3)-(2x+9x-9)= | | r=3.47 | | x/y+2y | | 0.95x=100*.4 | | 5x^2+5y^2-60x+10y+165=0 | | 0.95x=100*.5 | | (7x-5)(7x-5)= | | .5x^2-5x-5.5=0 | | (-6x^2y)(x^9y^3)= | | -2x+ky=-7 | | (8x+3)(x^2-5x+1)= | | 2/x+2/y | | 10+4*4= | | x/-5 | | S+87.8=31.1 | | 1.25x-3.25=81 | | (9x-4)(4x+5)= | | -16t^2+32t+10=16 | | 5x-(0.345-x)=5x+0.713 | | 1.25x+3.25=81 | | 8(6x+5)= | | 3.5n+6.4=42.5 | | -16x^2+30x+225=0 |

Equations solver categories